Análisis de la Composición y Estructura de la Comunidad de Mamíferos del Parque Estatal Cerro ''El Faro'' - Reséndiz Tovilla, Lidia Wintzin (Universidad Autónoma Metropolitana. Unidad Xochimilco, 2025)
The study analyzes the composition and structure of medium and large mammals in the Cerro El Faro State Park (PECEF), a Protected Natural Area located in the State of México, through the use of camera traps installed between April 2021 and September 2022. This park, with an area of 40 hectares, is home to high biodiversity, but faces significant pressures from urban growth and the presence of domestic animals. The main objective was to evaluate the biodiversity of mammals in the area to contribute to its conservation and sustainable management. During the monitoring, 8 species of mammals belonging to 5 orders and 8 families were recorded, of which 6 are wild and 2 are domestic: Canis lupus familiaris (dog) and Felis catus (cat). The most frequent species were the rabbit (Sylvilagus floridanus) and the opossum (Didelphis virginiana), while the dog was the species with the highest number of records, reflecting the influence of urban proximity and the recreational activity of nearby inhabitants. Camera traps located in less disturbed areas recorded greater species richness, suggesting that habitats less impacted by human activities are more favorable for wildlife. Activity patterns revealed that most species are nocturnal or crepuscular, with greater activity between 4:00 a.m. and 10:00 p.m. Domestic species, particularly dogs, have a significant presence, which can generate pressure on wild species by acting as predators or competitors. In addition, low overall diversity was observed compared to other protected areas in the State of México, possibly due to habitat fragmentation, the growth of irregular settlements, and constant interaction with domestic animals. The study concludes that biodiversity in PECEF is at risk due to human intervention and recommends increasing monitoring and conservation efforts. It is crucial to implement measures to control the access of domestic animals to the park and reduce anthropogenic pressures. These actions will ensure the conservation of mammals and the maintenance of the ...